REDUCTION OF CARDIOVASCULAR COMPLICATIONS OF MODERN HYPOGLYCEMIC THERAPY OF DIABETES MELLITUS TYPE 2: "FLORENTINE HERESY" - A. A. Aleksandrov (Столичная издательская компания, 2016)
The classic hypoglycemic agents include biguanides, sulfonylurea drugs, meglitinides, glitazones and alpha-glucosidase inhibitors. Modern algorithm of hypoglycemic therapy in the first step considers lifestyle modification and metformin monotherapy, the second step - the combined therapy. However, the effect of combined hypoglycemic therapy on long-term cardiovascular prognosis in patients with type 2 diabetes mellitus is studied insufficiently. Combined therapy with glibenclamide and metformin can result in adverse cardiovascular effects, so that long term therapy should be avoided in patients with coronary heart disease. Adequate pharmacological approaches to hyperglycemia correction should be elaborated.